Sex, Mitochondria, and Genetic Rescue. (February 2016) - Havird, Justin C.; Fitzpatrick, Sarah W.; Kronenberger, John; Funk, W. Chris; Angeloni, Lisa M.; Sloan, Daniel B.
Abstract : Genetic rescue is a potentially effective management tool to offset the effects of reduced genetic diversity in imperiled populations. However, implementation requires complex choices. Here we address the consequences of introducing males versus females, highlighting the possibility that introduced females might lead to maladapted mitonuclear genomes and reduced offspring fitness.